2017
DOI: 10.1097/aap.0000000000000593
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Regional Anesthesia and Inpatient Rehabilitation for Pediatric Complex Regional Pain Syndrome

Abstract: Continuous regional anesthesia may be an option to facilitate intensive rehabilitation for selected pediatric patients with CRPS. Further research should help clarify the role of regional anesthesia in a comprehensive management program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…series [15], 39% of the sample did not clinically improve the pain symptoms, and 43% had no functional advantages. Nevertheless, the authors suggested the treatment in addition to an active PT + CBT protocol.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…series [15], 39% of the sample did not clinically improve the pain symptoms, and 43% had no functional advantages. Nevertheless, the authors suggested the treatment in addition to an active PT + CBT protocol.…”
Section: Discussionmentioning
confidence: 89%
“…Several treatments have been described [2], including acupuncture, transcranial magnetic stimulation, and invasive procedures, but the e cacy has been proven for the combination of physical and cognitive behavioural therapy and some pharmacological treatments only. The most established treatment is a programme of physical rehabilitation and cognitive behavioural therapy [15]. The goal is to restore normal function, increase the joint motion range, load tolerance and strength, and concurrently assist the child in accepting and managing the pain [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar adverse events were recorded ( p = 0.77). Donado and colleagues [ 15 ] investigated the use of continuous regional anesthesia (epidural or peripheral catheter) in subjects refractory to PT + CBT. Their data showed significant changes between admission and discharge for pain ( p < 0.0001), without significant changes throughout the 4-month period after admission ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Several treatments have been described [ 2 ], including acupuncture, transcranial magnetic stimulation and invasive procedures, but the efficacy has been proven for the combination of physical and cognitive behavioral therapy and only pharmacological treatments. The most established treatment is a program of physical rehabilitation and cognitive behavioral therapy [ 15 ]. The goal is to restore normal function, increase the joint motion range and load tolerance and strength and concurrently assist the child in accepting and managing the pain [ 2 ].…”
Section: Discussionmentioning
confidence: 99%